Doctors' thinking about the system as a threat to patient safety - Waring, Justin (SAGE, 2007)
‘Systems thinking’ is an important feature of the emerging ‘patient safety’ agenda. As a key component of a ‘safety culture’, it encourages clinicians to look past individual error to recognise the latent factors that threaten safety. This paper investigates whether current medical thinking is commensurate with the idea of ‘systems thinking’ together with its implications for policy. The findings are based on qualitative semistructured interviews with specialist physicians working within one NHS District General Hospital in the English Midlands. It is shown that, rather then favouring a 'person-centred’ perspective, doctors readily identify ‘the system’ as a threat to patient safety. This is not necessarily a reflection of the prevailing safety discourse or knowledge of policy, but reflects a tacit understanding of how services are (dis)organised. This line of thinking serves to mitigate individual wrong-doing and protect professional credibility by encouraging doctors to accept and accommodate the shortcomings of the system, rather than participate in new forms of organisational learning.